ERROR-FREE ACTIVITY OF THE INFORMATION PROCESSING OPERATOR: TARGETED TRAINING CONCEPT - Sazhko, H.; Pirsl, D. (Problems of Engineer-Pedagogical Education, 2023)
The relevance of the paper is reflected in the investigation of the activities structure in numerous modern professions, with a significant share devoted to an operator’s activities. Therefore, a problem of ensuring the quality of operators’ activities, and the error-free and timely computer processing of text, graphic and figurative information must be solved. Assumptions that the high-quality training of operators is based on the profound knowledge of the qualitative and quantitative characteristics of the errors flows are verified. The concept of the targeted training of information processing operator to perform error-free activity is highlighted and described. The essence of the targeted training is to develop the theoretical foundations of a methodological system for the formation of the operator’s readiness to perform error-free activity, taking into account the professional level of individual groups of students. The correct construction of the concept is enhanced if it takes the form of a set of clearly separable statements. The set is complete, consistent and contains elements that cannot be inferred from each other. The consistency and non-deduction of the provisions were proved within the framework of the presented study, and the completeness was proved based on the theory of ergonomic training of engineers-teachers specializing in computers to perform professional activity. Experimental ergonomic research enhances the introduction of the targeted training of an information processing operator into the practice of vocational training, along with mass and individual training. Targeted training allows one to rely on the laws of mathematical learning theory. Prospects for further research would include conducting an experiment to find an experimental coefficient characterizing the operator’s ability to learn; conducting a comparative pedagogical experiment to determine the pedagogical effectiveness of the targeted training of computer typing operators, and the introduction of the innovative methodological support into the educational process.